Review of Research Progress on the Impact of Submarine Groundwater Discharge on Pockmark Formation and Evolution - Zhengrong Zhang; Hongxian Shan; Xuezhi Feng; Zhentian Jia; Long Jiang; Siming Wang; Chaoqi Zhu (Journal of Marine Science and Engineering, 2025)
Pockmarks are globally distributed geomorphic features exhibiting diverse morphologies. Their geometric characteristics are commonly quantified by the radius-to-depth ratio. The evolutionary process of these features typically follows a cyclical pattern comprising initiation, expansion, stabilization, and decline. Submarine groundwater discharge (SGD), a seasonally modulated land–sea exchange process, exerts a significant influence on the formation and evolution of pockmarks. This influence is mediated through hydrodynamic forcing effects, sediment redistribution, and coupled chemical–biological interactions. This review systematically examines the formation mechanisms, evolutionary patterns, and primary controlling factors of pockmarks induced by SGD. It integrates recent research developments and global case studies to elucidate the dynamic interplay of multiple influencing factors. This study emphasizes the significance of interdisciplinary approaches in marine geological research and identifies key areas for future investigation. These insights aim to enhance risk assessment frameworks for marine hazards and inform marine spatial planning strategies.